A STUDY THE BEHAVIOR AND ATTITUDE TOWARDS HEALTH CARE OF PROFESSIONAL ATHLETES WHO HAVE HAD SPORTS INJURIES THAT CAUSED PROBLEMS IN TRAINING AND COMPETITION : A CASE STUDY OF PROFESSIONAL FUTSAL ATHLETES OF AN EDUCATIONAL INSTITUTION IN MIN BURI, BANGKOK - Hongsala, Narongpakron; Kaewpraek , Sumeth; Kitkhuntod, Arissa (Journal of Modern Sport Management, 2024)
This research has a specific objective to understand the health care behaviors and attitudes of professional athletes who have had sports injuries that impact their training and competition. Professional futsal athletes from an educational institution in Min Buri, Bangkok were recruited as a case study. The researcher used qualitative research by in-depth interviews and non-participant observation. The main informants were 10 professional futsal players. The results of the study found that most of the key informants were under 30 years old and lived in Bangkok and its vicinity. Most of the key informants weighed between 60-70 kilograms and were between 160-170 centimeters tall. Most of the key informants had lower body injuries, especially knees, and took more than 1 month to recover. The key informants played sports according to the correct program and were at high risk of collisions during training. The results of the study found that 1) Athletes exercised or played sports appropriately, but were at risk of injuries from training and could be a problem for the competition. 2) Although the athletes slept for more than 6 hours, it is recommended that they adjust their bedtime to wake up earlier and ensure they eat breakfast on time. 3) Athletes should eat appropriately, such as eat all 5 food groups, but should increase their knowledge of nutritional principles so that athletes can eat appropriately. Keywords: Injury, Professional Athlete, Behavior and Attitude